Análisis de la sentencia emitida por la Corte Nacional de Justicia.- Sala Laboral. Juicio laboral No. 902-2011 sobre recurso de casación (Jurisprudencia) - Urquizo Guevara, Medardo Efraín (2015)
This analysis is about the judgment of the Labor Chamber of the National Court of Justice in the cassation appeal brought by Norma Janeth Burgos Cabrera. The petitioner based its claim on the third ground for cassation appeal (article 3 of the Cassation Appeal Law), claiming the lack of the evaluation of documentary evidence in the judgment of the Appeal Court of Guayas Province (Labor and Juvenile Chamber). This judgment might have ignored the existence of the labor relationship between the petitioner and Reyventas Inc.